Open source approaches to establishing Roseobacter clade bacteria as synthetic biology chassis for biogeoengineering - Borg, Yanika; Grigonyte, Aurelija Marija; Boeing, Philipp; Wolfenden, Bethan; Smith, Patrick; Beaufoy, William; Rose, Simon; Ratisai, Tonderai; Zaikin, Alexey; Nesbeth, Darren N. (PeerJ, 2016)
Aim. The nascent field of bio-geoengineering stands to benefit from synthetic biologists’ efforts to standardise, and in so doing democratise, biomolecular research methods. Roseobacter clade bacteria comprise 15–20% of oceanic bacterio-plankton communities, making them a prime candidate for establishment of synthetic biology chassis for bio-geoengineering activities such as bioremediation of oceanic waste plastic. Developments such as the increasing affordability of DNA synthesis and laboratory automation continue to foster the establishment of a global ‘do-it-yourself’ research community alongside the more traditional arenas of academe and industry. As a collaborative group of citizen, student and professional scientists we sought to test the following hypotheses: (i) that an incubator capable of cultivating bacterial cells can be constructed entirely from non-laboratory items, (ii) that marine bacteria from the Roseobacter clade can be established as a genetically tractable synthetic biology chassis using plasmids conforming to the BioBrickTM standard and finally, (iii) that identifying and subcloning genes from a Roseobacter clade species can readily by achieved by citizen scientists using open source cloning and bioinformatic tools. Method. We cultivated three Roseobacter species, Roseobacter denitrificans, Oceanobulbus indolifexand Dinoroseobacter shibae. For each species we measured chloramphenicol sensitivity, viability over 11 weeks of glycerol-based cryopreservation and tested the effectiveness of a series of electroporation and heat shock protocols for transformation using a variety of plasmid types. We also attempted construction of an incubator-shaker device using only publicly available components. Finally, a subgroup comprising citizen scientists designed and attempted a procedure for isolating the cold resistance anf1 gene from Oceanobulbus indolifexcells and subcloning it into a BioBrickTM formatted plasmid. Results. All species were stable over 11 weeks of glycerol cryopreservation, sensitive to 17 µg/mL chloramphenicol and resistant to transformation using the conditions and plasmids tested. An incubator-shaker device, ‘UCLHack-12’ was assembled and used to cultivate sufficient quantity of Oceanobulbus indolifexcells to enable isolation of the anf1 gene and its subcloning into a plasmid to generate the BioBrickTM BBa_K729016. Conclusion.The process of ‘de-skilling’ biomolecular techniques, particularly for relatively under-investigated organisms, is still on-going. However, our successful cell growth and DNA manipulation experiments serve to indicate the types of capabilities that are now available to citizen scientists. Science democratised in this way can make a positive contribution to the debate around the use of bio-geoengineering to address oceanic pollution or climate change.
Keywords: Synthetic biology; Biogeoengineering; Open source; Molecular biology; Marine biology; Bioremediation; DIYbio